Vietnamese Citizen Participation in Local Governance - Trang, Tang Thi Thu (Journal of Ecohumanism, 2024)
Local governance is characterized by the interaction between government agencies and people in the local social management process, in which people are encouraged to actively play a part in government management activities as regulated by laws. This study addresses the people's rights to directly and indirectly participate in local governance activities in Vietnam. A survey of 360 people from 4 localities representing three regions of Vietnam, including Thai Binh province, Hung Yen province (Northern region), Quang Binh province (Central region), Ca Mau province (Northern region) was conducted to evaluate citizen participation in governance activities of commune-level authorities. The results show that the citizen participation in local governance activities do exist, but are limited to the direct participation. To some extent, the people also have rights to self-determine local issues on infrastructure construction and public welfare projects with their own contributions; however, their self-development of programs and projects and proposals to local authorities for implementation has not been clearly demonstrated. These findings suggest expanding the people's rights to participate in local governance activities as innovations for the improvement local governance effectiveness.